Propiedades físicas y mecánicas de la madera Huayruro como material de construcción - Medina Ldrogo, José Artemio (1999)
The present research work aims to provide engineers as a tool of consultation for the design of structural wood. The development of this theme makes use of the standards ITINTEC, INIMVI E-101, AFNOR and consists of chapters IX. Tests to determine the physical properties such as: moisture content, density and shrinkage using ITINTEC standards. Mechanical properties: compression parallel to the fiber, compression Perpendicular to the fiber, static bending (beams and specimens), cut parallel to the fiber, fiber-parallel drive, was made in order to calculate the allowable efforts, module of elasticity, effort to the proportional limit deformation to the limit Proporcional·. For these tests was done with ITINTEC standards and are structurally classified according to the standards INIMVI E-101 through the test on beams to bending. For complementary tests, bending dynamics, Perpendicular traction to the fiber, cleavage Per...